Are we overdiagnosing multisystem inflammatory syndrome in children (MIS-C)? A case series of children with bacterial infection mimicking MIS-C - Kumar, Anil; Rajvanshi, Nikhil; Prabhakaran, Kalyana; Saini, Lokesh; Goyal, Jagdish Prasad; Kumar, Prawin (The Journal of Infection in Developing Countries, 2024)
Introduction: Multisystem inflammatory syndrome in children (MIS-C) is a serious hyperinflammatory condition associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Usually, the diagnosis of MIS-C is made by criteria defined by international organizations, which include specific clinical features, laboratory findings, and evidence of SARS-CoV-2 infection. We hereby present a case series of three children. The objective of this case series, involving chart review of medical records of children admitted with MIS-C, is to emphasize that the features of MIS-C may overlap with other conditions. Case presentation: Three children were presented with MIS-C based on World Health Organization (WHO) criteria and given treatment for the same. However, due to persistent symptoms, they were further worked up and diagnosed to have underlying bacterial infections which included liver abscess, enteric fever, or urinary tract infection. Conclusions: The criteria for MIS-C may overlap with other conditions, particularly bacterial infection that may lead to overdiagnosis of MIS-C. Therefore, one should be very careful in making an MIS-C diagnosis and other differential diagnoses should be considered when the symptoms persist or worsen.